High‐throughput purification tools for rapid upstream process development are interchangeable for biologics. Issue 2 (3rd July 2015) - Petroff, Matthew G.; Feliciano, Jessika; Pollard, David J.; Li, Hong; Linden, Thomas O.; Pollard, Jennifer M.
Abstract : Upstream process development of biologics is not only productivity‐driven but also quality‐driven. Typically, most quality attributes are not directly measurable in cell culture samples due to low product concentration and purity, thus requiring some level of sample purification. As higher throughput upstream technologies become available, sample purification is becoming a bottleneck in limiting the number and types of cell culture samples that can be analyzed. The application of high‐throughput, microscale protein purification techniques has the potential to address and expand this capability. In this work, the affinity capture step of an IgG1 mAb was adapted to fit resin‐plate, resin‐tip, and mini‐column formats in an attempt to approximate the packed‐column performance by optimizing parameters such as contact time, liquid/resin ratio, and loading to produce a yield of ≥70% yield. A representative cell culture supernatant was purified using both the optimized microscale and conventional techniques, and analyzed using a comprehensive panel of product quality assays. This direct comparison demonstrated that each technique generates product of equivalent purity across a wide range of feed conditions. The analytical comparability suggests that any of the conventional and high‐throughput methods are interchangeable for biologics, allowing flexible development of an end‐to‐end integrated high‐throughput strategy.